2004
DOI: 10.1002/cncr.20406
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of patients with hematologic malignancies who develop fever accompanied by pulmonary infiltrates

Abstract: BACKGROUNDThe mortality rate associated with fever accompanied by pulmonary infiltrates after chemotherapy for hematologic malignancies remains higher than the corresponding rate associated with febrile neutropenia without pulmonary infiltrates. Nonetheless, few studies have focused on the factors that predict outcome for patients with lung infiltrates. The purpose of the current study was to construct a risk model for clinical use by assessing the factors that affect outcome for patients with fever and pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…Pneumonia remains a major challenge in acute leukemia treatment 5, 8, 9, 30 with a substantial mortality 27, 31. Prospective reports have demonstrated the feasibility and safety of outpatient management and early discharge of acute leukemia by inclusion of broad‐spectrum AP 11, 12, 17, 18, 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pneumonia remains a major challenge in acute leukemia treatment 5, 8, 9, 30 with a substantial mortality 27, 31. Prospective reports have demonstrated the feasibility and safety of outpatient management and early discharge of acute leukemia by inclusion of broad‐spectrum AP 11, 12, 17, 18, 20.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia, defined as X‐ray‐verified pulmonary infiltrate in addition to fever 27, was the primary outcome based on guidelines from Statens Serum Institut, Copenhagen, Denmark (https://www.ssi.dk/) 28 and the British National Guideline Centre 29. Imaging investigations were performed at the included sites with radiologists blinded to study group allocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the review of the primary literature found six studies addressing the predictive value of body temperature. The patients who were involved had already been diagnosed with febrile neutropenia, and the cut-off used in five studies was 39°C [16][17][18][19][20] . In those studies, temperature was an unreliable predictor of poor outcome.…”
Section: Temperaturementioning
confidence: 99%
“…The aim of our recently published risk model was to predict the outcome of hematologic patients with fever and pulmonary infiltrates. We found that CRP, serum albumin level, and trend in white blood cell (WBC) count were predictive of pulmonary infiltrate outcome [7]. However, it is also substantial to recognize factors predicting the etiology of pulmonary infiltrates.…”
Section: Introductionmentioning
confidence: 95%